Library and information services: impact on patient care quality. Issue 8 (7th October 2014) - Gard Marshall, Joanne; Craft Morgan, Jennifer; A. Thompson, Cheryl; L. Wells, Amber
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore library and information service impact on patient care quality. Design/methodology/approach – A large-scale critical incident survey of physicians and residents at 56 library sites serving 118 hospitals in the USA and Canada. Respondents were asked to base their answers on a recent incident in which they had used library resources to search for information related to a specific clinical case. Findings – Of 4, 520 respondents, 75 percent said that they definitely or probably handled patient care differently using information obtained through the library. In a multivariate analysis, three summary clinical outcome measures were used as value and impact indicators: first, time saved; second, patient care changes; and third, adverse events avoided. The outcomes were examined in relation to four information access methods: first, asking librarian for assistance; second, performing search in a physical library; third, searching library's web site; or fourth, searching library resources on an institutional intranet. All library access methods had consistently positive relationships with the clinical outcomes, providing evidence that library services have a positive impact on patient care quality. Originality/value – Electronic collections and services provided by the library and the librarian contribute to patient care quality.